2009
DOI: 10.4161/cbt.8.10.8146
|View full text |Cite
|
Sign up to set email alerts
|

The herbal extract Iberogast® improves jejunal integrity in rats with 5-Fluorouracil (5-FU)-induced mucositis

Abstract: There is an acute need for the development of effective therapies for mucositis, a debilitating side effect of cancer chemotherapy. Iberogast ® is a herbal extract reported to possess anti-inflammatory properties. We investigated Iberogast ® for its potential to reduce the severity of 5-Fluorouracil (FU)-induced mucositis in rats. Rats were allocated to three treatment groups (n = 8) and gavaged daily with a 10% solution of Iberogast ® or water from day 0 to day 8. Rats were injected intraperitoneally with 5-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 36 publications
6
51
0
1
Order By: Relevance
“…Although the aetiology of UC is not entirely understood, recent advances in biotechnology have resulted in the development of novel nutraceutical treatment approaches for these diseases, to complement conventional treatments [2]. These 'nutraceutical' therapies include Lyprinol [11], certain probiotics [12], growth factors [13], and plant sourced extracts such as Iberogast TM [14] and more recently, Grape Seed Extract (GSE) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the aetiology of UC is not entirely understood, recent advances in biotechnology have resulted in the development of novel nutraceutical treatment approaches for these diseases, to complement conventional treatments [2]. These 'nutraceutical' therapies include Lyprinol [11], certain probiotics [12], growth factors [13], and plant sourced extracts such as Iberogast TM [14] and more recently, Grape Seed Extract (GSE) [15].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that inhibition of DNA synthesis, DNA damage and the production of reactive oxygen species by chemotherapy impair the metabolism in progenitor cells and cause inhibition of mitosis and increase of apoptosis [1]. Wright et al [32] also found that 5-FU administration results in increased apoptosis and decreased cellularity in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…118 Indeed, recently, Iberogast has been tested for its therapeutic efficacies on 5-fluorouracil-induced mucositis in rats. 38 Iberogast improved the histopathological features of mucosa, which were damaged by 5-fluorouracil injection. Villus height and crypt depth were increased significantly in Iberogast-fed rats treated with 5-fluorouracil.…”
Section: Plant Extracts and Intestinal Mucositismentioning
confidence: 91%
“…36 Moreover, recently, probiotic-derived factors have begun to show promise at preventing mucositis in vivo and in vitro. 35,37 In addition, there are now early indications that antioxidant and anti-inflammatory constituents in plant extracts, such as Iberogast 38 and grape seed extract, 39 and animal-sourced oils, such as Lyprinol 40 and Emu oil, 41 could have utility in preventing mucositis.…”
Section: Treatment Of Mucositismentioning
confidence: 99%